Effects of arm insulation on physiological responses during running in the cold - Ito, R.; Yamashita, N.; Matsumoto, T. (The Journal of Sports Medicine and Physical Fitness, 2018)
BACKGROUND: Individuals who exercise outdoors in winter expose themselves to cold conditions, which have detrimental effects on physiological responses and exercise performance. Many runners wear arm warmers to protect against cold. However, the effects of these warmers remain unclear. This study aimed to determine the effect of arm insulation on physiological responses during running in a cold environment. METHODS: Twelve healthy men (mean±SD age, 22.4±3.9 years; height, 1.71±0.07 m; mass, 66.9±8.1 kg; maximal oxygen consumption, 52.3±4.79 mL/kg/min) ran on a treadmill at an intensity of 70% maximal oxygen consumption for 30 minutes in a climatic chamber at 5 °C wearing (ARM) or not wearing (CON) a tight-fitting polyester sleeve on the forearm. RESULTS: During the first 10 minutes of exercise, esophageal temperature was significantly higher (P<0.05) in ARM than in CON. Weighted mean skin temperature was significantly higher (P<0.05) in ARM than in CON. Thermal sensation was significantly higher (P<0.05) in ARM than in CON during rest and during the first 10 minutes of exercise. Plasma lactate concentration was significantly lower (P<0.05) in ARM than in CON at 10 minutes, and plasma norepinephrine concentration was significantly lower (P<0.05) in ARM than in CON at 10 and 20 minutes. CONCLUSIONS: Higher esophageal temperature and thermal sensation and lower plasma norepinephrine concentration indicate that arm insulation suppressed cold stress and attenuated the production of plasma lactate in the early stages of exercise.